Analysis of The Influence of E-Customer Satisfaction, E-Service Quality and Digital Sales Promotion on Customers Repurchase Intention Through Digital Wallet Shopeepay - Yuni Dharta, Firdaus; Risdwiyanto, Andriya; Herlandi Putra, Irsan; Utami, Eva Yuniarti; Ambarwati, Retnoning (Jurnal Sistim Informasi dan Teknologi, 2023)
The purpose of this study is to determine whether e-service quality and sales promotion have an impact on e-customer satisfaction and repurchase intention. The precise sample size for this study is not available. However, it is comprised of residents of Indonesia's five biggest cities who have used the e-wallet app. Users of e-wallet applications who met the requirements of never using one and not utilizing the application for less than three months made up the study's sample. Purposeful sampling, a nonprobability sampling technique, was applied in this study. The study sample consisted of one hundred respondents in total. Papers, questionnaires, and a literature review gathered data for this study. This inquiry employed the path analysis method. Several inferences can be made in light of the study's findings and the following discussion, including the following: Sales promotions and online customer happiness are correlated. The caliber of e-services has some bearing on e-customer happiness. E-customer satisfaction is simultaneously influenced by sales marketing and the quality of service. Sales promotions have an impact on consumers' propensity to make further purchases. The caliber of the e-service partially influences repurchase intentions. E-customer satisfaction has some bearing on repurchase intentions. Repurchase intentions equally impact sales promotion, e-service quality, and e-customer satisfaction.